The Influence of Inequality, Labor, Poverty, and HDI on Economic Growth in East Nusa Tenggara - Adzana Isanti Wulandari; Hendry Cahyono (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2026)
This study investigates how income inequality (measured by the Gini coefficient), labor force participation, poverty levels, and human capital quality (represented by the Human Development Index) affect economic growth in East Nusa Tenggara (NTT) Province. Using time-series data from 2010 to 2024 sourced from official statistics, the study employs a multiple linear regression model that meets all classical assumptions such as normality, absence of multicollinearity, no heteroscedasticity, and no autocorrelation. The results indicate that all four factors positively and significantly contribute to economic growth, with the HDI standing out as the most influential variable, highlighting the vital importance of human capital development. Despite observed economic growth, the region faces a paradox where inequality and poverty remain widespread, signifying that growth in NTT is not inclusive and largely driven by low-productivity, informal sectors. The study calls for urgent policy interventions aimed at strengthening human capital through better education and healthcare, alongside transforming the labor market by shifting employment towards the formal sector. Examining these variables together within NTT’s socio-economic framework, this research offers crucial insights for promoting sustainable and inclusive growth in developing regions.